Implementation of Food Security Policy in Tomohon City - Singal, Ereine Stelma; Singal, Ereine Stelma; Kairupan, Sisca B.; Kairupan, Sisca B.; Tarore, Steven (Technium Social Sciences Journal, 2025)
Food security is very important in the context of national development to form quality, independent and prosperous Indonesian people through the realization of sufficient, safe, quality, nutritious and diverse food availability and evenly distributed throughout Indonesia. This research aims to find out, analyze and describe matters related to the Implementation of Food Security Policy in Tomohon City. This research uses descriptive qualitative method. The results showed that there were main problems in the 5 indicators studied, namely 1) Policy interest indicators: unbalanced food distribution and price fluctuations, low public awareness of local food consumption and lack of comprehensive policies; 2) Policy benefit indicators: policies do not meet local needs, lack of coordination, and limited extension, education and infrastructure; 3) Policy objectives Indicators: limited access and low understanding of farmers to adaptive agricultural technology, as well as obstacles in accessing agricultural insurance programs; 4) Implementing apparatus indicators: there are infrastructure challenges, lack of coordination between agencies, and limited skills of policy implementing apparatus; 5) Indicators of financial resources: unbalanced budget allocations, lack of diversification of funding sources, and suboptimal use of funds. The suggestions or recommendations in this study are improving the distribution system and comprehensive policies, improving coordination between related parties, strengthening the capacity of farmers and agricultural technology, increasing the capacity of implementing apparatus, and optimizing financial resources.